Toll-like receptor 4 polymorphisms and their haplotypes modulate the risk of developing diabetic retinopathy in type 2 diabetes patients - Singh K.; Kant S.; Singh V.K.; Agrawal N.K.; Gupta S.K.; Singh K. (My University, 2025)
Purpose: Persistent infl ammation and impaired neovascularization in type 2 diabetes mellitus (T2DM) patients may lead to development of macro- and microvascular complications. Diabetic retinopathy (DR) is one of the secondary microvascular complications of T2DM. Improper activation of the innate immune system may be an important contributor in the pathophysiology of DR. Toll-like receptor 4 (TLR4) is an important mediator of innate immunity, and genetic alterations in TLR4 support infl ammation in the hyperglycemic condition. The present work was designed to investigate whether the TLR4 single nucleotide polymorphisms (SNPs) rs4986790, rs4986791, rs10759931, rs1927911, and rs1927914 are associated with DR in a north Indian population. Methods: The study group of 698 individuals (128 DR, 250 T2DM, 320 controls) was genotyped by PCR-RFLP. Haplotype and linkage disequilibrium between SNPs were determined using Haploview software. Results: Combined risk genotypes of TLR4 SNPs rs10759931 (odds ratio [OR] 1.50, p = 0.05) and rs1927914 (OR 1.48, p = 0.05) were found to be significantly associated with pathogenesis of DR. A total of 14 haplotypes with frequency >1% were obtained using Haploview software. Haplotypes ACATC (37.5%) and ACATT (14.8%) were the two most common haplotypes obtained. Conclusions: Results of the present case-control study that included 698 north Indian subjects suggested that TLR4 SNPs rs10759931 and rs1927914 modulate the risk of DR in T2DM cases. Association analysis using haplotypes showed none of the haplotypes were associated with either susceptibility or resistance to DR in a north Indian population. © 2014 Molecular Vision.